Pengaruh E-Wom terhadap Purchase Intention di Media Sosial: Studi Kasus pada Skintific - Widjaja, Beatrice Adabella; Kristanto, Debora Naftaliana; Yosevina, Christiana Tercia; Sumarlin, Antonius W (Kajian Branding Indonesia, 2025)
This study aims to investigate the influence of Electronic Word of Mouth on consumer Purchase Intention, focusing on the case of Skintific, a skincare brand active on online platforms such as Instagram and TikTok. Data collection will be conducted through an online questionnaire disseminated via social media platforms. The study will be conducted based on an online survey and will utilize the Ordinal scale with statistical evaluations using SPSS and AMOS software, focusing on respondents residing in the Jabodetabek area. These findings suggest that recommendations, reviews, and discussions exchanged by social media users can influence consumer purchasing decisions regarding Skintific products. The practical implications of these findings underscore the importance of maintaining brand reputation, strengthening consumer interactions, and designing marketing campaigns that promote positive messages on social media to enhance purchase intention and overall business success.